AEDESTROYER a proposed robotic solution to control dengue in Malaysia - Marzuki, N.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
Dengue is one of the most popular diseases in the world, including Malaysia. The number of reported cases of dengue keeps increasing year by year. This dengue fever is caused by viruses that are transmitted by mosquitoes that are well known as aedes or Aegypti. This fever leads to headache, exhaustion, rush, vomiting and muscle pain. Another critical dengue problem is Dengue Haemorrhagic Fever that can cause a serious bleeding shock and death. No specific medicine found to treat dengue infection up until today, which forces the public to depend on individual immune system. In order to control dengue cases, a lot of approaches being conducted by the government but the number of dengue cases keep increasing. This paper proposes a new idea to control dengue cases using a robotic approach, named as AEDESTROYER. The research investigates the potential of the application in Malaysia and the technical design of the prototype is briefly discussed. This research is at its preliminary stage and hence, solid testing results are not available. Â© 2014 IEEE.